Effects of BTEX Exposure on Hematological and C-Reactive-Protein in Professional and Non Professional Motorcycle Drivers in Cotonou/Benin - AYI FANOU, Lucie; ATINDEHOU, MENONVE MEGNISSE; ANAGO, AHOÉFA AMÉLÉ EUGÉNIE; Cachon, Boris Fresnel; Agassounon Djikpo Tchibozo, Micheline (My University, 2020)
Benzene, toluene, ethylbenzene and xylene (BTEX) are toxic volatile organic compounds (VOCs) present in polluted ambient air. Air pollution can affect human health through chronic or acute exposure to fumes from vehicles and motorcycles. Our study aims to evaluate the concentration of BTEX in the ambient air and its effects on the biological parameters of motorcycle drivers. We recruited 30 pairs of professional (30) and non-professional (30) motorcycle drivers in Cotonou / Benin. The 3MR3500 organic vapor monitor badges were worn around the necks of these drivers during 8 hours of motorcycle driving. The badges analysis were carried out with gas chromatography flame ionization detector (GC-FID). Biological parameters were measured using the CHEM-7 erba spectrophotometer and the Sysmex XT 4000i spectrophotometer. Our results showed that the means concentrations of BTEX are higher for professional drivers than non-professionals. A statistically significant difference was observed between the two groups with p <0.05. The mean concentrations of BTEX were 77.00 ± 5.45; 245.91 ± 18.99; 72.53 ± 7.54 professional and 67.25 ± 14.54 μg / m3 for professional motorcycle drivers and 25.87 ± 6.51; 139.75 ± 19.08; 64.26 ± 4.99 and 41.60 ± 00.00 μg / m3 for non-professional motorcycle drivers. Likewise, the biological parameters (hematological and immunological ultra-sensitive C-reactive protein) were also different between the two groups (p <0.05). Professional motorcycle drivers are more exposed and affected to BTEX than non-professionals drivers. This exposure may alter biological parameters.
Keywords: BTEX; professional motorcycle drivers; non-professional motorcycle drivers; sensitive CRP; hematological parameters